Difficultés de la participation en recherche-action : retour d'expériences de modélisation d'accompagnement en appui à l'aménagement du territoire au Sénégal et à la Réunion - William Daré; Sigrid Aubert; A Bah; Aurélie Botta; I Diop-Gaye; Christine Fourage; G Lajoie; Grégoire Leclerc (VertigO)
How can scientists help institutions and local stakeholders be more involved in land use and territorial management processes? Decentralization of land use management is far from complete in Senegal and La Réunion Island. Despite exhaustive legislation, local populations remain little involved in the decisions that affect their land. This is partly due to the difficulties in understanding and managing the complexity of dynamic and interacting social and environmental systems. The Domino project aims at accompanying decision processes by proposing to stakeholders to build and explore scenarios of land use management. This experiment in participatory modelling, done on two contrasting sites, is built on complex partnership dynamics. In this paper we do a comparative analysis of difficulties raised by the involvement of partners in companion modelling. We conclude by discussing the need for quality process in action-research.